Thammasat University Experiences Toward “Management System for Copyright, Academic Work and Thesis (MyCat)” from 2014 - 2016 - Chancheewa, Srichan (Journal of Multidisciplinary Academic Research and Development (JMARD), 2018)
One mission of the Thammasat University Libraries is to make information accessible to all. We will discuss the learning experiences at Thammasat University Library in terms of the innovative plagiarism software MyCat (Management System for Copyright, Academic Work, and Thesis), an application for checking duplicates in student dissertations, theses, and reports as well as staff papers. Correctly checking Thai script is a key requirement in this cutting-edge product, since the Thai language has its own characters and has not been as globalized as other major languages. MyCat is a software for checking information correctness. It provides connectivity between university standards and actual data to be distributed among libraries for collaborative sharing. Using it, Thammasat collaborated with the National Electronics and Computer Technology Center (NECTEC), a division of the National Science andTechnology Development Agency (NSTDA). NECTEC implemented the software, using Thammasat University dissertation work flows, developing and suggesting groundbreaking ways to demonstrate this powerful plagiarism software to the public as a practical benefit to society. This collaboration is an example of a library using local, lower-cost products with more effective impact on the local academic scene. Ideally in the future, widespread collaboration among Thai universities for checking duplicates may extend to the regional level for the purpose of data sharing. To develop into an effective tool, one essential requirement is that it opens a pathway to new learning.